Organizational Culture, Self-Efficacy, and ICT Skills as a Mediator of Educator Performance in Aviation Vocational Education - Tommy Hendratno; Suhendra Suhendra; Yossa Istiadi (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Within the vocational education sector, educator performance serves as a fundamental determinant of graduate quality; however, it frequently encounters constraints arising from rigid institutional structures and inadequate digital proficiency. Objective: This study examines the influence of organizational culture, self-efficacy, and Information and Communication Technology (ICT) skills, both directly and indirectly, on the performance of educators at the Indonesian Aviation Polytechnic (PPI) Curug. Methods: A quantitative research design employing a survey method was applied to 85 respondents consisting of lecturers and instructors. Path analysis using SPSS software served as the primary data analysis technique. Results: The findings indicate that (1) organizational culture has a direct positive effect on educator performance (βy1 = 0.024); (2) self-efficacy has a direct positive effect on educator performance (βy2 = 0.488); (3) ICT skills have a direct positive effect on educator performance (βy3 = 0.499); (4) organizational culture has a direct positive effect on ICT skills (βz1 = 0.563); and (5) self-efficacy has a direct positive effect on ICT skills (βz2 = 0.328). Furthermore, ICT skills function as a mediating variable by mediating (6) the relationship between organizational culture and educator performance (β = 0.698), and (7) the relationship between self-efficacy and educator performance (β = 0.639). Conclusion: These findings confirm that ICT skills serve as a significant mediating construct in the relationship between organizational culture and self-efficacy on educator performance. The study recommends that PPI Curug management prioritize competency-based ICT training programs and self-efficacy enhancement strategies as integrated components of human resource development policy to improve overall educator performance in the digital era of aviation vocational education.